A SURVEY RESEARCH OF ENGLISH DEPARTMENT STUDENTS’ PROFICIENCY LEVEL SCORE OF DUOLINGO ENGLISH PRACTICE TEST - Wali, Asri Indah; Syarif, Andi Rachmawati; Syahriani, Ririn (Universitas PGRI Semarang, 2025)
Assessing students' English proficiency is a crucial aspect in evaluating learning effectiveness, particularly in English Language Education study programs. However, limited research has examined student achievement in the context of online test-based evaluation. This study aimed to determine students' English proficiency levels based on Duolingo English Practice Test (DEPT) scores and examine their implications for English language teaching in higher education. This study employed a descriptive quantitative approach through a survey of 60 students from semesters 2, 4, and 6. Data were obtained through independent DEPT score collection uploaded by respondents via Google Form. The results showed that most students were at a moderate proficiency level, with average scores ranging from 75 to 89. Only a small proportion of students achieved the high category, and there was significant variation between individuals and between semesters. These findings suggest a need for re-evaluation of implemented learning strategies and the importance of increasing students' exposure to contextual language practices. Programs such as Student Talent Search and English Language Day can be supportive tools, but their implementation needs to be optimized to have a significant impact on improving language proficiency. This study contributes to highlighting the importance of synergy between learning evaluation, student motivation, and the quality of language teaching strategies in higher education.